RETRACTED ARTICLE: EFL learners’ boredom coping strategies: the role of teacher-student rapport and support - Yanbo Zhang (BMC Psychology)
Abstract Background A significant issue in the language education context is examining the coping strategies that learners apply to combat boredom in the class environment. As a significant contextual element affecting different dimensions of learners’ acquisition, teacher support in general education has been extensively studied but widely neglected in the English as a Foreign Language (EFL) setting. Also, having a relationship with a teacher can help a learner cope better with school challenges as the teacher can act as a reference for the learner. Methods To this end, 268 EFL learners participated to fill out the three scales namely, Teacher Support, Teacher-Student Rapport (T-SR), and learners’ Boredom Coping Strategies (BCS). Results Using multiple regressions, the results revealed that there are constructive links between these concepts as they affect learners’ BCS, and both T-SR and teacher support were predictors of learners’ BCS while the better predictor was teacher support. Conclusions As a result, it can be assumed that these two elements can enhance the students’ BCS in language acquisition which ends in declining boredom. Additionally, this research may have further implications for the team members of language teaching in academic environments.